Experimental Study on the Influence of Soil Structure Index on Loess Permeability - Feng Yue; Xin Ren; Xuelang Wang; Wentong Tian (Advances in Materials Science and Engineering)
In order to study the effects of dry density and initial water content on the permeability characteristics of loess, the saturated permeability tests of undisturbed loess and remolded loess were carried out in Lanzhou New Area. The anisotropy of undisturbed loess under two factors is analyzed and compared, and the permeability difference between undisturbed loess and remolded loess is also analyzed. The results show that the structure of loess has an important impact on the permeability characteristics, and the dry density is an important structural parameter. The natural structure of undisturbed loess has obvious anisotropy. Under different pore conditions and water contents, it will show the anisotropic behavior of permeability. The influence of water content on permeability is mainly reflected in the influence on the properties of cement between soil particle skeletons. Under different dry density conditions, the influence of water content on permeability is different. When the pore structure is relatively compact, the influence of water content is more obvious. In practical engineering, these two factors need to be comprehensively considered in order to accurately describe the permeability distribution of loess. This study can provide some theoretical guidance for the construction of relevant loess projects.